Wellness-enhancing effects of the canine growth hormone releasing hormone therapy mediated by plasmid and electroporation in healthy old dogs - Ryu, Min-Ok; Kim, Sung-moon; Kim, J. Joseph; Namkung, Hyun; Jung, Ho Kyoung; Nam, Hee Jin; Reed, Charles C.; Lim, Ga-Hyun; Kim, Eun Jin; Youn, Hwa-Young (Frontiers in Veterinary Science, 2025)
Aging leads to increased disease susceptibility and weakened immunity, a condition known as immunosenescence. The growth hormone-releasing hormone (GHRH)/growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis plays a key role in both somatic growth and immune modulation. This study evaluated the clinical and immunological effects of a canine GHRH-encoding plasmid delivered by electroporation in 30 healthy senior dogs (aged 10–16 years). Dogs received a single intramuscular injection and were monitored over 180 days. Significant improvements were observed in clinical scores, with 90% of dogs showing increased well-being based on owner-assessed measures including appetite, activity, and exercise tolerance. Limb thickness, used as a surrogate for muscle mass, significantly increased in both hindlimbs by day 180. While mean serum IGF-1 concentrations did not change overall, post-hoc stratification revealed that dogs with low baseline IGF-1 (<90 ng/mL) showed substantial increases, whereas those with high baseline levels tended to decrease. This bidirectional modulation suggests feedback-sensitive regulation of the GHRH-GH-IGF-1 axis. Flow cytometry demonstrated increases in total CD3+ T cells, as well as naïve CD4+ and CD8+ T cell subsets, indicating a potential delay in immunosenescence. The therapy was well-tolerated, with no serious adverse effects reported; hematologic abnormalities and gastrointestinal symptoms were transient and resolved without intervention. These findings suggest that GHRH-encoding plasmid therapy may improve clinical condition and modulate immune function in aging dogs, warranting further investigation into its long-term efficacy and potential applications.